Loom magic creatures! : 25 awesome animals and mythical beings for a rainbow of critters - Thomas, Becky; Sweeney, Monica (Sky Pony Press, 2014)
Learn to make these super imaginative, out-of-this-world projects that will take your rubber band loom projects to the next level. Wow everyone around you with fun and wacky critters. Here are step-by-step instructions and bright color photographs to show you how to make the coolest rubber band projects out there.